2020
DOI: 10.1186/s42649-020-00036-5
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of the silk spinning system in the caddisworm, Hydatophylax nigrovittatus (Trichoptera: Limnephilidae)

Abstract: Silk is produced by a variety of insects, but only silk made by terrestrial arthropods has been examined in detail. To fill the gap, this study was designed to understand the silk spinning system of aquatic insect. The larvae of caddis flies, Hydatophylax nigrovittatus produce silk through a pair of labial silk glands and use raw silk to protect themselves in the aquatic environment. The result of this study clearly shows that although silk fibers are made under aquatic conditions, the cellular silk production… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This part produces a thin axial thread of unknown composition located in the middle of fibroin filament [ 17 ]. This may be a peculiarity of a small group of species because such axial thread has not been observed in any other species [ 1 , 10 ]. Remarkably, the proposed MSG in S. marmorata seems to produce both fibroin and the adhesive coating [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This part produces a thin axial thread of unknown composition located in the middle of fibroin filament [ 17 ]. This may be a peculiarity of a small group of species because such axial thread has not been observed in any other species [ 1 , 10 ]. Remarkably, the proposed MSG in S. marmorata seems to produce both fibroin and the adhesive coating [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the proposed MSG in S. marmorata seems to produce both fibroin and the adhesive coating [ 17 ]. Another study by Kim et al (2020) investigated the morphology of SGs using electron microscopy in the limnephilid caddisfly Hydatophylax nigrovittatus [ 10 ]. They divided the SG into ASG and PSG and found that both parts contain different secretory cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations